Effects of Anticoccidial Vaccination and Taraxacum officinale Extract on the Growth Performance, Biochemical Parameters, Immunity, and Intestinal Morphology of Eimeria-Challenged Chickens - Anna Arczewska-Włosek; Sylwester Świątkiewicz; Ewa Tomaszewska; Siemowit Muszyński; Piotr Dobrowolski; Damian Józefiak (Life, 2023)
A total of 160 Ross 308 male chickens were used in a 2 × 2 factorial design to examine the effects of anticoccidial vaccination (ACV; lack or 1× dose recommended by the manufacturer) and dietary supplementation with Taraxacum officinale (dandelion) extract (DE; with or without) on growth performance, immunity, biochemical parameters, and intestinal morphology in broiler chickens challenged with Eimeria spp. At 20 days of age, all birds were challenged with a 25× dose of ACV, including Eimeria acervulina, E. maxima, E. mitis, and E. tenella. No interaction between ACV and DE was observed in terms of growth performance. Vaccinated birds showed increased feed intake (FI) and feed conversion ratio (FCR) during the 11–20 day period. Meanwhile, DE supplementation led to decreased FI and body weight gain (BWG) during the 1–10 day period. ACV effectively induced immunity against Eimeria, as evidenced by reduced oocyst shedding and less intestinal lesions, decreased levels of pro-inflammatory interleukin-6, and improved BWG during both the post infection (PI) period (21–35 days) and the entire growth period. DE supplementation lowered FCR and increased BWG during the 35–42 day period, increased the concentration of butyric acid in the cecal digesta, and lowered oocyst shedding PI. In vaccinated birds, DE elevated levels of plasma total protein and immunoglobulin M, and influenced tight junction proteins zonula occludens-1 and claudin-3, indicating a more robust epithelial barrier. DE also lowered alanine aminotransferase activity in unvaccinated birds. Both ACV and DE independently improved intestinal morphology in the jejunum, decreasing crypt depth and increasing the villus height-to-crypt ratio. These findings suggest that both ACV and DE could be effective strategies for managing coccidiosis in broiler chickens.